Spousal age differences and women's contraceptive use in sub-Saharan Africa - Pearl S. Kyei; Ayaga A. Bawah (BMC, 2024)
Abstract Background This study examines the likelihood of contraceptive use among married women in sub-Saharan Africa, focusing on the influence of spousal age difference. Methods Binary logistic regressions predicting contraceptive use were estimated using a sample of 478,193 women in first union from 29 sub-Saharan African countries spanning two decades from 1999 to 2022. The data were sourced from the Demographic and Health Surveys (DHS). Results The regression results indicate that spousal age difference is negatively correlated with the likelihood of contraceptive use with each additional year reducing the odds of using contraception by 1.1 percent. The association between the two variables has remained largely consistent over time. The findings also show substantial variation in the influence of spousal age differences on contraceptive use ranging from statistically significant and negative odds in some countries to not statistically significant but positive odds in others. Measures of female autonomy, education and healthcare decision-making, had a modest influence on the size and significance of the association between spousal age difference and contraceptive use. Conclusions The relationship between spousal age difference and contraceptive use is of concern given the prevalence of age-disparate relationships in the context. These findings add to the literature on the potentially negative implications of age-disparate relationships, while highlighting that the association is not uniformly negative across countries.